The influence of a non-aqueous phase liquid (NAPL) and chemical oxidant application on perfluoroalkyl acid (PFAA) fate and transport. (1st April 2016) - McKenzie, Erica R.; Siegrist, Robert L.; McCray, John E.; Higgins, Christopher P.
Abstract: One dimensional column experiments were conducted using saturated porous media containing residual trichloroethylene (TCE) to understand the effects of non-aqueous phase liquids (NAPLs) and chemical oxidation on perfluoroalkyl acid (PFAA) fate and transport. Observed retardation factors and data from supporting batch studies suggested that TCE provides additional sorption capacity that can increase PFAA retardation (i.e., decreased mobility), though the mechanisms remain unclear. Treatment with persulfate activated with FeCl2 and citric acid, catalyzed hydrogen peroxide (CHP), or permanganate did not result in oxidative transformations of PFAAs. However, impacts on PFAA sorption were apparent, and enhanced sorption was substantial in the persulfate-treated columns. In contrast, PFAA transport was accelerated in permanganate- and CHP-treated columns. Ultimately, PFAA transport in NAPL contaminated groundwater is likely influenced by porous media properties, NAPL characteristics, and water quality properties, each of which can change due to chemical oxidant treatment. For contaminated sites for which ISCO is a viable treatment option, changes to PFAA transport and the implications thereof should be included as a component of the remediation evaluation and selection process. Graphical abstract: Highlights: Chemical oxidant effects on PFAA fate and transport in porous media were studied. TCE sorbed PFAAs, where sorption increased with increasing PFAA chain length. PFAAs were not transformed by chemical oxidation, but their transport was affected. Aqueous and geochemistry changes likely impacted PFAA transport.